2009
DOI: 10.2353/ajpath.2009.090107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Manipulation of Dysferlin Expression in Skeletal Muscle

Abstract: Mutations in the gene DYSF, which codes for the protein dysferlin, underlie Miyoshi myopathy and limb-girdle muscular dystrophy 2B in humans and produce a slowly progressing skeletal muscle degenerative disease in mice. Dysferlin is a Ca 2؉ -sensing, regulatory protein that is involved in membrane repair after injury. To assess the function of dysferlin in healthy and dystrophic skeletal muscle, we generated skeletal muscle-specific transgenic mice with threefold overexpression of this protein. These mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 22 publications
5
56
0
Order By: Relevance
“…Serum CK levels of the dysferlinnull/Tg4 mice were normal before or after exercise, but those of the dysferlin-null were elevated as reported before ( Figure 3D). Consistent with a recent report (42), these data suggest that the presence of dysferlin in skeletal muscle protects muscle from damage even in the presence of a dysferlin-deficient immune system. Furthermore, quantitative RT-PCR examination of the quadriceps muscles from the dysferlin-null/Tg4 mice suggests that transgenic expression of dysferlin normalized the expression of the complement factors C1qA and CFB ( Figure 3E).…”
Section: Figuresupporting
confidence: 81%
“…Serum CK levels of the dysferlinnull/Tg4 mice were normal before or after exercise, but those of the dysferlin-null were elevated as reported before ( Figure 3D). Consistent with a recent report (42), these data suggest that the presence of dysferlin in skeletal muscle protects muscle from damage even in the presence of a dysferlin-deficient immune system. Furthermore, quantitative RT-PCR examination of the quadriceps muscles from the dysferlin-null/Tg4 mice suggests that transgenic expression of dysferlin normalized the expression of the complement factors C1qA and CFB ( Figure 3E).…”
Section: Figuresupporting
confidence: 81%
“…Millay et al showed that replacement of the dysferlin gene in AJ mice completely rescued muscle pathology and fully restored muscular force [48]. The AAV vector is the most commonly used viral vector in muscle gene therapy; however, there are major technical issues associated with using AAV in therapeutic approaches, including the limited packaging size of AAV vectors, which is below the size of dysferlin mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the content of PC in rmd/rmd mice skeletal muscle or alterations in the lipid composition, represented by changes in the PC/PE ratio, may lead to muscular dystrophy in this mouse model ( 10 ). This spontaneous recessive mutation in Chkb in rmd/rmd mice shares several phenotypic characteristics with the dysferlin null mouse, which is a model for limb-girdle dystrophy type 2B myopathy ( 177 ). Dysferlin is a sarcolemma-associated protein that is important in skeletal membrane repair using a Ca 2+ -dependent resealing mechanism ( 178 ).…”
Section: Rostrocaudal Muscular Dystrophymentioning
confidence: 99%